Wacana Pra-Pemilu 2024 pada Kolom Opini Jawapos.Com – Pendekatan Metaforis Konseptual - Fidiyanti, Murni; Syaikhu, Ahmad; Rosyidi, Zudan; Efendi, Rachmat; Irsyadi, Achmad Naufal; Hanafi, Imam (Universitas Muhammadiyah Surabaya, 2025)
Elections are among the most significant political events in a democratic country, where the legitimacy to exercise power is granted to elected political officials. The mass media can serve as an arena where various political actors compete for public attention and seek to influence public opinion. This study aims to identify conceptual metaphorical elements in the opinion columns of the online mass media platform JawaPos.com. The research is situated within the field of linguistics, as discourse and mass media both utilize language as an instrumental tool. This study employs a linguistic approach, utilizing note-taking techniques for data collection and referential methods for data analysis. The research concludes that the syntactic elements of discourse within opinion columns contain conceptual metaphorical elements that function as a form of mind control. The audience, as listeners and readers, negotiates with their thoughts, experiences, and intuitions in response to opinions written by experts and published in particular mass media.